Metode Takhrij Hadits Dalam Menakar Hadits Nabi - Muhammad Qomarullah (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2016)
Takhrij urgency in studying the hadith also is to provide convenience for people who want to practice after learning that a hadith is hadith maqbul (acceptable). And otherwise do not practice it is discovered that a hadith is mardud (rejected).